Nuclear modernization in the 21st century - Warren, Aiden; Baxter, Philip M. (Modern security studies., 2020)
"This book examines the global strategic and policy implications of the modernization efforts of the nuclear weapons powers and considers the effects modernization could have on the relations between these nuclear weapon powers and the larger impact upon efforts to curb nuclear weapons, both in terms of horizontal and vertical proliferation"--